Concurrent validity of the Microsoft Kinect for Windows v2 for measuring spatiotemporal gait parameters. Issue 9 (September 2016) - Dolatabadi, Elham; Taati, Babak; Mihailidis, Alex
Highlights: We evaluated the performance of the Kinect v2 comparing with the GAITRite system. Kinect v2 can accurately measure spatio-temporal gait comparing with GAITRite. Kinect v2 can measure gait features at usual and fast pace and dual task walking. This study suggests that Kinect v2 is a valid clinical tool for gait measurements. This study offers others to use Kinect v2 for gait assessment in any environment. Abstract: This paper presents a study to evaluate the concurrent validity of the Microsoft Kinect for Windows v2 for measuring the spatiotemporal parameters of gait. Twenty healthy adults performed several sequences of walks across a GAITRite mat under three different conditions: usual pace, fast pace, and dual task. Each walking sequence was simultaneously captured with two Kinect for Windows v2 and the GAITRite system. An automated algorithm was employed to extract various spatiotemporal features including stance time, step length, step time and gait velocity from the recorded Kinect v2 sequences. Accuracy in terms of reliability, concurrent validity and limits of agreement was examined for each gait feature under different walking conditions. The 95% Bland–Altman limits of agreement were narrow enough for the Kinect v2 to be a valid tool for measuring all reported spatiotemporal parameters of gait in all three conditions. An excellent intraclass correlation coefficient ( ICC 2, 1 ) ranging from 0.9 to 0.98 was observed for all gait measures across different walking conditions. The inter trial reliability of all gait parameters were shown to be strong for all walking types ( ICC 3, 1 > 0.73). The results of this study suggest that the Kinect for Windows v2 has the capacity to measure selected spatiotemporal gait parameters for healthy adults.